2022
DOI: 10.1186/s12864-022-09000-x
|View full text |Cite
|
Sign up to set email alerts
|

De novo genome assembly and genome skims reveal LTRs dominate the genome of a limestone endemic Mountainsnail (Oreohelix idahoensis)

Abstract: Background Calcareous outcrops, rocky areas composed of calcium carbonate (CaCO3), often host a diverse, specialized, and threatened biomineralizing fauna. Despite the repeated evolution of physiological and morphological adaptations to colonize these mineral rich substrates, there is a lack of genomic resources for calcareous rock endemic species. This has hampered our ability to understand the genomic mechanisms underlying calcareous rock specialization and manage these threatened species. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 88 publications
2
2
0
Order By: Relevance
“…However, given that only 76.6% of PacBio CLR reads mapped to the final genome assembly (Table 1 ), it is likely that many repeat regions remain unresolved. The proportion of annotated genes in the Berghia genome was also quite high (77.8% with BLASTP hits), consistent with other published gastropod genomes [ 86 – 88 ].…”
Section: Discussionsupporting
confidence: 88%
“…However, given that only 76.6% of PacBio CLR reads mapped to the final genome assembly (Table 1 ), it is likely that many repeat regions remain unresolved. The proportion of annotated genes in the Berghia genome was also quite high (77.8% with BLASTP hits), consistent with other published gastropod genomes [ 86 – 88 ].…”
Section: Discussionsupporting
confidence: 88%
“…However, given that only 76.6% of PacBio CLR reads mapped to the final genome assembly (Table 1), it is likely that many repeat regions remain unresolved. The proportion of annotated genes in the Berghia genome was also quite high (77.8% with BLASTP hits), consistent with other published gastropod genomes [5557].…”
Section: Discussionsupporting
confidence: 88%
“…Once annotated, comparisons of genome assemblies from different individuals, populations or species can capture the full range of genome variation, including SNPs, repetitive elements, copy‐number variants and structural variation (Dominguez Del Angel et al., 2018). For example, annotation of both repetitive elements and genic regions in a threatened and endemic land snail, Oreohelix idahoensis , revealed that expansions of long terminal repeats are responsible for differences in both genome size and gene composition, specifically expanding gene families related to stress and biomineralization compared to other Oreohelix species (Linscott et al., 2022). Structural variation that would go undetected in more fragmented assemblies can also provide critical information about the maintenance of polymorphisms within species.…”
Section: Introductionmentioning
confidence: 99%